No one is talking about this [large type] - Lockwood, Patricia (Random House Large Print, 2021)
As this urgent, genre-defying book opens, a woman who has recently been elevated to prominence for her social media posts travels around the world to meet her adoring fans. She is overwhelmed by navigating the new language and etiquette of what she terms "the portal," where she grapples with an unshakable conviction that a vast chorus of voices is now dictating her thoughts. When existential threats--from climate change and economic precariousness to the rise of an unnamed dictator and an epidemic of loneliness--begin to loom, she posts her way deeper into the portal's void. An avalanche of images, details, and references accumulate to form a landscape that is post-sense, post-irony, post-everything. "Are we in hell?" the people of the portal ask themselves. "Are we all just going to keep doing this until we die?" Suddenly, two texts from her mother pierce the fray: "Something has gone wrong," and "How soon can you get here?" As real life and its stakes collide with the increasingly absurd antics of the portal, the woman confronts a world that seems to contain both an abundance of proof that there is goodness, empathy, and justice in the universe, and a deluge of evidence to the contrary.